A cross-sectional study on physical and sedentary activity and health-related quality of life in institutionalized vs. non-institutionalized elderly - Tomas-Carus, Pablo (2015)
Aims: to compare the physical activity, sedentary activity and health-related quality of life (HRQoL) in institutionalized vs. non-institutionalized elderly, and to establish a pattern of relationship and prediction of physical and sedentary activity with physical and mental components of HRQoL. Methods: the sample consisted of 383 elderly with ≥ 75 years old (n=187 institutionalized and n=196 non-institutionalized). Were administered the International Physical Activity Questionnaire (IPAQ) and Short Form 36 Health Survey (SF-36) for evaluated the physical and sedentary activity and HRQoL. Also was used the Mini Mental State Examination (MMSE) as exclusion criteria for cognitive problems in the elderly. Results: differences between institutionalized and non-institutionalized elderly were found in moderate-intensity activities and walking, a favour of non-institutionalized. The institutionalized elderly remain more minutes in sedentary activity. Also, were observed differences between both groups in physical component of HRQoL, a favour of non-institutionalized elderly. The mental component remained unchanged. The multivariate regression analyses showed that physical activity predicted the physical (8 to 12%) and mental (5 to 8%) components of HRQoL for institutionalized and non-institutionalized elderly. Conclusions: non-institutionalized elderly were more physically active, spent less time in sedentary activity and showed better perception physical component of HRQoL that institutionalized elderly. An important and encouraging result of this study was that physical activity is a predictor of improved physical and mental component of HRQoL for institutionalized and non-institutionalized elderly.